Em busca de um entendimento completo acerca do emaranhamento - Daniel Cavalcanti Santos (2006)
A great effort has been devoted to understand Quantum InformationTheory. This interest comes from the fact that this field has given us advanced methods to process and store information. Among these proposals we can cite the teleportation, the quantum cryptography, and the quantum computation. Interestingly, entanglement is the main resource that puts the quantum approach in a higher level than the classical counterpart. On the other hand, the theory of entanglement allows also a better understanding of physical phenomena already treated by the fields of condensed matter, statistical physics, and quantum optics among others. In this dissertation we aim to review the main topics concerning the Theory of Entanglement and propose new results on this theme as well. Firstly, we will discuss how the notion of entanglement raises naturally, how to determine whether a state is entangled, and how to quantify it. Moving on to the three qubit context,we will show a tomographic process able to determine the quantum stateof a system using only two detectors. It will be shown the connection between multipartite entanglement and the exceptions to our process. In the multipartite scenario we will obtain novel results in the formalism of the theory.Specifically, we study the question: are all maximally entangled statespure? While for bipartite systems almost all entanglement quantifiers agree in a positive answer, in a more general context this is not the case. Indeed, we will show a multipartite entanglement quantifier for which all maximally entangled states are pure. Finally, we address some questions on identical particle entanglement, i.e.: the entanglement coming just from the indistinguishabilityof quantum particles.